Key parameters in determining energy generated by CPV modules. (1st September 2014) - Kurtz, Sarah; Muller, Matthew; Jordan, Dirk; Ghosal, Kanchan; Fisher, Brent; Verlinden, Pierre; Hashimoto, Jun; Riley, Daniel
Abstract: We identify the key inputs and measurement data needed for accurate energy rating of concentrator photovoltaic (CPV) modules based on field observations of multiple CPV modules. Acceptance angle is shown to correlate with the observed module‐level performance ratio (PR) for the modules studied. Using power ratings based on concentrator standard test conditions, PRs between 90% and 95% were observed during the summers with up to ~10% lower PRs during the winters. A module fabricated by Semprius showed 94% ±0.7% PR over almost 2 years with seasonal variation in PR of less than 1% showing how a module with relatively large acceptance angle may show very consistent average efficiency (calculated from the energy generated relative to the energy available), potentially simplifying energy ratings. The application of the results for translation of energy rating from one location to another is discussed, concluding that most of the translation differences may be correlated with temperature differences between sites with the largest variation happening when optical efficiency depends on temperature. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Field observations of CPV modules are examined to identify critical parameters for energy rating CPV modules. Acceptance angle correlates with performance ratio (PR) for the modules studied. PR of 90–95% was observed during the summers with up to ~10% lower PRs during colder times as shown in the figure. A Semprius module showed 94% ± 0.7% PR with seasonal variation in PR of <1% showing how CPV modules may show very consistent average efficiency, potentially simplifying energy ratings.